Metal particles and method for producing same

The described method addresses the challenges of existing metal particle production techniques by employing an oxidation-reduction reaction with specific dispersants to produce metal particles with enhanced porosity, surface area, and sphericality, achieving efficient and cost-effective mass production.

JP2025514737AActive Publication Date: 2025-05-09SUZHOU AIMEITE ENTERPRISE MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024561680
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-05-25
Filing Date
2023-03-13
Publication Date
2025-05-09
Estimated Expiration
2043-03-13

AI Technical Summary

Technical Problem

Current methods for producing metal particles, such as biological templating and liquid phase reduction, are complex, expensive, and difficult to scale for mass production, often resulting in uneven particle size distribution and harsh reaction conditions.

Method used

A method involving an oxidation-reduction reaction of a metal source-containing oxidation agent with a reducing agent in the presence of first and second dispersants, where the first dispersant includes a low molecular weight organic solvent and nanoparticles, and the second dispersant includes a high molecular weight organic solvent, to produce metal particles with high porosity, large specific surface area, and high sphericality.

Benefits of technology

The method achieves metal particles with a high shrinkage ratio, large specific surface area, and high sphericality, while simplifying the production process and reducing costs, enabling efficient mass production with improved particle uniformity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025514737000001_ABST
    Figure 2025514737000001_ABST
Patent Text Reader

Abstract

The present invention provides metal particles and a method for producing the same. The method for producing the metal particles includes a step of obtaining the metal particles by subjecting a metal source-containing oxidizing agent and a reducing agent to an oxidation-reduction reaction in the presence of a first dispersant and a second dispersant, the first dispersant including a first organic solvent having a low molecular weight and at least one type of nanoparticles, and the second dispersant including a second organic solvent having a high molecular weight. The metal particles of the present invention have advantages such as a high shrinkage ratio, a large specific surface area, and a high sphericity, and the production method is simple and efficient.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention is in the field of metallic materials, and in particular relates to metallic particles and methods for producing same. [Background technology]

[0002] Precious metals mainly refer to eight metallic elements including gold, silver, and platinum group metals (ruthenium, rhodium, palladium, osmium, iridium, platinum). Many of these metals have beautiful colors and high chemical stability, and under normal conditions, they rarely react with other chemicals. Precious metal powders have important applications in the manufacture of solar cell pastes such as electronic devices and conductive adhesives, and silver powder, in particular, as a conductive filler, is currently the most widely used precious metal powder.

[0003] The properties of metal powders include not only particle size but also morphology and internal structure, which play a decisive role in the properties of metal pastes. Internally porous metal powders are a new material developed in recent years, which have a large specific surface area, low specific gravity, and excellent permeability due to the small metal powder particles and many internal voids. Hollow metal powders have attracted renewed attention due to their wide range of applications in catalysis, electrochemistry, drug delivery, etc.

[0004] At present, the main methods for producing metal particles include biological template method, liquid-phase reduction method, chemical vapor deposition method, thermal decomposition method, etc., but the template method has a complicated process and high cost. The liquid-phase reduction method is expensive, and the liquid-phase microwave method has a strict reaction and is difficult to mass-produce. For example, CN101905330A discloses a method for producing hollow silver produced by Streptococcus thermophilus, and CN101912970A discloses a method for producing spherical porous silver powder by spray method, but there are problems such as harsh reaction conditions, large amount of powder, and uneven particle size distribution.

[0005] Therefore, there remains a need for a manufacturing method that can produce metal particles with high porosity, large specific surface area, and excellent sphericity, and that has a simple process and is low cost. Summary of the Invention [Problem to be solved by the invention]

[0006] The object of the present invention is to overcome the above-mentioned shortcomings in the prior art and provide a method for producing metal particles, which have the advantages of high shrinkage ratio, large specific surface area, high sphericity, etc., and the production method is simple and efficient. [Means for solving the problem]

[0007] In order to achieve the above object, in one aspect, the present invention provides a method for producing metal particles comprising the steps of: subjecting a metal source-containing oxidizing agent and a reducing agent to an oxidation-reduction reaction in the presence of a first dispersing agent and a second dispersing agent; the first dispersant comprises a first low molecular weight organic solvent and at least one type of nanoparticles; and The second dispersant contains a second organic solvent having a high molecular weight.

[0008] In the manufacturing method according to the present invention, the presence of the first dispersant and the second dispersant plays an important role in the manufacture of metal particles having advantages such as high shrinkage ratio, large specific surface area, and high sphericity, because the low molecular weight organic solvent in the first dispersant can effectively coat the nanoparticles to form a coating aggregate. The polymer of the high molecular weight organic solvent in the second dispersant can well intercalate with the coating aggregate to form a homogeneous phase system, which makes it difficult for the nanoparticles to aggregate in the one-stage reaction of oxidation and reduction. More specifically, in the early stage of the oxidation and reduction reaction, the action of the organic solvent in the first dispersant can prevent the metal particles generated in the early reaction of oxidation and reduction from being stuck together to form a metal diaphragm structure. After a few seconds or minutes from the reaction, the first stage metal particles are formed, and voids exist inside the formed metal particles. Then, the newly generated first stage metal particles are polymerized in the environment of the second dispersant to form metal particles, and such metal particles also contain large voids inside. In the two-stage reaction, the high molecular weight organic polymer of the second dispersant forms large voids between the metal particles in the polymerization process of the metal particles.

[0009] As described above, the metal source-containing oxidizing agent and reducing agent of the present invention may carry out an oxidation-reduction reaction in the presence of the first dispersant and the second dispersant, and there is no particular limitation on the initial system of the reaction and the order of addition of the oxidizing agent and the reducing agent. For example, the oxidizing agent may be added in advance to the system of the first dispersant and the second dispersant, and then the reducing agent may be added to carry out the oxidation-reduction reaction, or the reducing agent may be added in advance to the system of the first dispersant and the second dispersant, and then the oxidizing agent may be added to carry out the oxidation-reduction reaction, or the oxidizing agent and the reducing agent may be added in advance to the system of the first dispersant and the second dispersant, and then the oxidation-reduction reaction may be carried out. In other words, the oxidizing agent and the reducing agent of the present invention may be mixed with the system of the first dispersant and the second dispersant independently or simultaneously, but there is no particular limitation. The oxidizing agent and the reducing agent may also be provided by a supplementary supply method.

[0010] The first dispersant and the second dispersant of the present invention both contain an organic solvent, but the molecular weights of both organic solvents are different, i.e., the molecular weight of the organic solvent contained in the second dispersant (i.e., the second organic solvent) is higher than the molecular weight of the organic solvent contained in the first dispersant (i.e., the first organic solvent). In one embodiment of the present invention, the low molecular weight and the high molecular weight may be separated by a specific molecular weight, for example, 1200 Da. Thus, in this embodiment, the first organic solvent may be an organic solvent with a molecular weight of 1200 Da or less (e.g., 1000 Da or less, or 800 Da or less), and the second organic solvent may be an organic solvent with a molecular weight of more than 1200 Da (e.g., 1500 Da).

[0011] The first organic solvent and the second organic solvent are not particularly limited in type except for the difference in molecular weight. For example, in one embodiment of the present invention, the first organic solvent and the second organic solvent are each independently at least one selected from organic acids (including, but not limited to, fatty acids), gum arabic, esters, ethers, ether esters, ketones, amines, alcohols, pyridines, and pyrrolidones. That is, the first organic solvent and the second organic solvent may be the same or different, and may contain one or more of the above organic solvents.

[0012] More specifically, in one embodiment of the present invention, the first organic solvent is a fatty acid and its salt, an alkyl sulfuric acid and its salt, an alkyl benzene sulfonic acid and its salt, a linear alkyl benzene sulfonic acid and its salt, a maleic acid and its salt, 1-vinylpyrrolidone, N-vinylpyrrolidone, methylpyrrolidone, polyoxyethylene lauryl ether triethanolamine sulfate, octylamine, ethanol, polyethylene glycol, alkyl triethanolamine sulfate, glycerol, an alkyl ether sulfate ester salt, sorbitol, sorbitan, polysorbate (Tween), sorbitan fatty acid ester (Span), lecithin, polysorbate dialkyldimethylammonium chloride, alkylpyridinium chloride, polyoxyethylene alkyl ether (AE), polyoxyethylene alkenyl ether (AL), polyoxyethylene aryl ether (PA ... The second organic solvent may be at least one selected from gum arabic, formaldehyde condensates of naphthalene sulfonates, polyacrylates, copolymer salts of vinyl compounds and carboxylic acid monomers, carboxymethyl cellulose, polyvinyl alcohol, polyethylene glycol, polyacrylic acid partial alkyl esters and / or polyalkylene polyamines, polyethyleneimine and / or aminoalkyl methacrylate copolymers, polyvinylpyrrolidone, polystyrene sulfonic acid, polyacrylic acid, polyoxyethylene alkyl ethers, and polyoxyethylene alkyl phenyl ethers, but is not limited thereto.

[0013] Furthermore, the first dispersant of the present invention further contains at least one type of nanoparticles, which may be at least one type selected from organic nanoclusters, non-metal oxides, simple metals, metal oxides, and inorganic metal salts, and preferably the size of the nanoparticles may be 0.1 to 90 nm (e.g., 0.1 nm, 0.2 nm, 0.5 nm, 1 nm, 2 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 70 nm or 90 nm, 1 to 50 nm, 0.1 to 40 nm, etc.).

[0014] More specifically, in one embodiment of the present invention, the organic nanoclusters may be at least one selected from cellulose and organic carbohydrates, the non-metal oxide may be at least one selected from oxides of silicon, carbon, and nitrogen (i.e., silicon oxide, carbon oxide, nitrogen oxide), the metal may be at least one selected from gold, silver, platinum, palladium, cobalt, copper, nickel, and zinc, the metal oxide may be at least one selected from oxides of gold, silver, platinum, palladium, cobalt, copper, nickel, and zinc, and the metal inorganic salt may be selected from, but is not limited to, metal sulfates and / or nitrates (e.g., sodium sulfate, ammonium sulfate, potassium sulfate, copper sulfate, ferrous sulfate, sodium nitrate, potassium nitrate, ferrous nitrate, or copper nitrate, etc.).

[0015] In the metal source-containing oxidizing agent of the present invention, the metal source (usually referring to metal ion) is reduced to a metal in an oxidation-reduction process, and therefore the metal source-containing oxidizing agent of the present invention may be any compound containing a metal ion, where the metal includes, but is not limited to, at least one of gold, silver, platinum, palladium, cobalt, copper, nickel, and zinc, or the metal may be, in particular, at least one of precious metals, such as gold, silver, and platinum group metals (ruthenium, rhodium, palladium, osmium, iridium, platinum). For example, in one embodiment of the present invention, the metal source-containing oxidizing agent may be at least one selected from inorganic metal salts, organic metal salts, and metal complexes.

[0016] More specifically, in one embodiment of the present invention, the inorganic salt may be at least one of, for example, carbonate, bicarbonate, phosphate, phosphite, hydrogen phosphate, nitrate, nitrite, hydrochloride, bromate, iodate, sulfate, sulfite, and bisulfate, and the organic salt may be, for example, acetate, adipate, aspartate, benzoate, benzenesulfonate, camphorsulfonate, citrate, cyclohexylamine sulfonate, ethylene disulfonate, formate, fumarate, glucoheptonate, gluconate, gluconate, or glycerol. The metal complex may be at least one of salts of the above-mentioned salts, such as phosphate, hexafluorophosphate, 2-hydroxyethanesulfonate, lactate, malate, maleate, malonate, methanesulfonate, methylsulfate, naphthoate, 2-naphthalenesulfonate, nicotinate, nitrate, oxalate, hexadecanoate, pyroglutamate, saccharate, stearate, salicylate, tannate, tartrate, tosylate, and trifluoroacetate, and the metal complex may be, for example, an ammonium salt or a metal ammonia solution.

[0017] Regarding the reducing agent of the present invention, in the manufacturing method of the present invention, the type of reducing agent is not particularly limited, and it is sufficient if it has sufficient reducing ability and can reduce the metal source in the oxidizing agent to a metal. For example, in one embodiment of the present invention, the reducing agent is a hydrazine-based agent (hydrazine, hydrazine monohydrate, phenylhydrazine, hydrazine sulfate, etc.), an amine-based agent (dimethylaminoethanol, triethylamine, octylamine, dimethylaminoborane, etc.), an organic acid-based agent (citric acid, ascorbic acid, tartaric acid, malic acid, malonic acid, or salts thereof, formic acid, formaldehyde, etc.), an alcohol-based agent (methanol, ethanol, isopropyl alcohol, ethylene glycol, diglycol, triglycol, tetraglycol, benzotriazole, etc.), an aldehyde-based agent (formaldehyde, acetaldehyde, propionaldehyde ... The reducing agent is at least one selected from hydrogen compound-based reducing agents (sodium borohydride, lithium borohydride, lithium triethylborohydride, lithium aluminum hydride, diisobutylaluminum hydride, tributyltin hydride, lithium tri-sec-butylborohydride, potassium tri-sec-butylborohydride, zinc borohydride, sodium acetoxyborohydride), transition metal salt-based reducing agents (iron sulfate, tin sulfate), pyrrolidone-based reducing agents (polyvinylpyrrolidone, 1-vinylpyrrolidone, N-vinylpyrrolidone, methylpyrrolidone), and hydroxylamine-based reducing agents (hydroxylamine sulfate, hydroxylamine nitrate).

[0018] Regarding the amounts of the first dispersant, the second dispersant, the oxidizing agent and the reducing agent used in the production method of the present invention, in one embodiment of the present invention, the molar amount of the reducing agent may be 0.1 to 9 times, preferably 0.5 to 7 times, more preferably 1 to 5 times (e.g., 1 time, 2 times, 3 times, 4 times or 5 times, preferably to complete the oxidation-reduction reaction) compared to the molar amount of the metal (i.e., metal source) in the oxidizing agent. If the amount of the reducing agent used is too low, unreduced metal may remain, and if the amount of the reducing agent used is too high, the reaction may be too fast, the number of aggregated particles may increase, and the deviation of the final particle size may increase. In another embodiment of the present invention, the weight of the first dispersant may be 0.1 to 40 wt% (e.g., 0.1 wt%, 0.5 wt%, 1 wt%, 5 wt%, 10 wt%, 20 wt%, or 40 wt%, etc.), the weight of the second dispersant may be 1 to 60 wt% (e.g., 1 wt%, 5 wt%, 10 wt%, 20 wt%, 40 wt%, or 60 wt%, etc.), and the weight of the nanoparticles may be 0.0001 to 1.0 wt% (e.g., 0.0001 wt%, 0.001 wt%, 0.01 wt%, 0.1 wt%, or 1 wt%, etc.), but preferably 0.005 to 0.01 wt%, relative to the weight of the metal (i.e., metal source) in the oxidizing agent.

[0019] The reaction conditions of the production method of the present invention may be room temperature or appropriately heated conditions. For example, in one embodiment of the present invention, the reaction may be carried out at a temperature of 1 to 90°C, preferably 20 to 80°C, more preferably 25 to 50°C (e.g., 25°C, 30°C, 35°C, 40°C, 45°C, or 50°C, etc.). In order to achieve a homogeneous reaction, the production method of the present invention may be carried out with stirring, and the stirring speed may be, for example, 5 rpm to 1000 rpm.

[0020] In particular, the manufacturing method of the present invention may include a step of adding a flocculant after or before the redox reaction, but it is also possible that it is not necessary to add a flocculant because of the selection of a different dispersant, which can change the charge potential on the particle and its surface that can be bonded to other particles, which can then be separated to obtain nano metal particles free of mother liquor. In one embodiment of the present invention, the flocculant may be selected from lipid compounds, carboxylic acid compounds or inorganic salts. More specifically, in one embodiment of the present invention, the lipid compound includes lipid precursors and derivatives thereof, such as saturated fatty acids and their salts or unsaturated fatty acids and their salts, and preferably, the saturated fatty acids are at least one selected from caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, and arachidic acid, the unsaturated fatty acids are at least one selected from oleic acid, linoleic acid, sorbic acid, linolenic acid, and arachidonic acid, the carboxylic acid compounds are at least one selected from compounds having a carbon-carbon double bond, dicarboxy compounds, and dihydroxy compounds, and the inorganic salts are at least one selected from sulfates, nitrates, and ammonium salts, but are not limited thereto. In another embodiment of the present invention, the amount of the flocculant added may be 0.001% to 20% (e.g., 0.001%, 0.01%, 0.1%, 1%, 10%, 15%, or 20%) of the weight of the metal particles.

[0021] In another aspect, the present invention also provides metal particles produced by the above method.

[0022] As described above, due to the action of the first dispersant and the second dispersant, the metal particles of the present invention obtained by the oxidation-reduction reaction have voids, and these voids include voids formed between the metal fine particles in the two-step reaction process in addition to the closed voids formed inside the metal fine particles in the one-step reaction process, and the voids between the metal fine particles may be open to the surface of the metal particles. Therefore, the metal particles according to the present invention have advantages such as a high shrinkage ratio, a large specific surface area, and a high sphericity, and can be applied to technical fields such as printed circuit boards and solar cells. In one embodiment of the present invention, the porosity of the metal particles may be 2.97% or more.

[0023] It should be understood that the endpoints of the ranges and any values ​​disclosed herein are not limited to the exact ranges or values, and that the ranges or values ​​include values ​​close to these ranges or values. In the case of numerical ranges, the endpoints of each range, the endpoints of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered as specifically disclosed herein.

[0024] Before describing the present invention in detail, it should be understood that the terms used herein are used only to describe certain embodiments and are not intended to limit the scope of the present invention, which is intended to be limited only by the appended claims. In order to more fully understand the invention described herein, the following terms are used. These definitions are as follows. Technical and scientific terms used herein have the same meaning as understood by one of ordinary skill in the art, unless otherwise defined. [Brief description of the drawings]

[0025] The drawings are included to provide a further understanding of the invention, constitute a part of this specification, and are intended to explain the invention together with the following specific embodiments, but not to limit the invention. [Figure 1]1 shows silver metal particles produced according to Example 1 of the present invention. [Diagram 2] 1 shows the results of observing a single silver metal particle produced by Example 2 of the present invention under a microscope, and shows that the surface of this particle has a porous structure. [Diagram 3] 1 shows the results of observing a single silver metal particle produced by Example 2 of the present invention under a microscope, which shows that one fine particle is not completely polymerized on the silver particle surface. [Figure 4] 1 shows the results of observing a single silver metal particle produced by Example 3 of the present invention under a microscope. [Diagram 5] 1 shows a cross-sectional view of a single particle in the silver metal particles produced by Example 1 of the present invention at a magnification of 80K. [Figure 6] 1 shows a cross-sectional view of a single particle in the silver metal particles produced by Example 2 of the present invention at a magnification of 50K. [Figure 7] 1 shows a cross-sectional view of another single particle of silver metal particles produced by Example 2 of the present invention at a magnification of 50K. [Figure 8] 1 shows a cross-sectional view of a single particle in a silver metal particle produced by Example 3 of the present invention at a magnification of 50K. [Figure 9] 1 shows a cross-sectional view of a single particle in a silver metal particle produced by Example 4 of the present invention at a magnification of 50K. [Figure 10] 1 shows a cross-sectional view of a single particle in a silver metal particle produced by Comparative Example 1 of the present invention at a magnification of 50K. [Figure 11] FIG. 10 is a partially enlarged view of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] Hereinafter, specific embodiments of the present invention will be described in detail. It should be understood that the specific embodiments described herein are only intended to explain and explain the present invention, and are not intended to limit the present invention.

[0027] In the following examples, FIB-SEM technology is used as a method for cutting metal particles, in which a gallium particle focused ion beam is used to cut the metal particles, and individual metal particles are cut so that the cross-section of the metal particles is exposed, and then a scanning electron microscope (SEM) is used to observe the cross-section of the particles.

[0028] Working Example Example 1 10 mL of sorbitol and 35 μg of 40-90 nm cellulose were mixed to obtain a first dispersant, and carboxymethyl cellulose was dissolved in 35 mL of water to prepare a solution with a mass concentration of 6.5% to obtain a second dispersant. The first dispersant and second dispersant produced above were mixed and stirred uniformly to obtain a dispersant system, and the solution was kept at a constant temperature of 35°C.

[0029] In addition, 17 g of silver nitrate was added to a beaker containing a certain amount of water and stirred uniformly, and the resulting silver nitrate solution was then added to the dispersant system, and then a 20% mass concentration solution containing 20 g of hydroxylamine sulfate was added while stirring, and after the reaction, oleic acid was added to obtain silver metal particles with a pore structure. The results of observation under a microscope are shown in Figure 1.

[0030] Example 2 15 mL of maleic acid and 20 μg of 20-50 nm nano silver oxide were mixed to obtain a first dispersant, and 3.5 g of gum arabic was dissolved in 50 mL of water to prepare a solution to obtain a second dispersant. The first and second dispersants were mixed and stirred uniformly to obtain a dispersant system, and the solution was kept at a constant temperature of 35°C.

[0031] A solution containing 20 g of ascorbic acid and having a mass concentration of 25% was prepared, and the ascorbic acid solution was added to the dispersant system prepared above. In addition, 17 g of silver nitrate was added to 50 mL of an aqueous solution and stirred uniformly, and then the silver nitrate solution was added to the above solution while stirring to react, and after the reaction, lauric acid was added to obtain silver metal particles having a pore structure. The microscopic results are shown in Figures 2 and 3. Of these, the particle diameter of the silver metal particles shown in Figure 2 is 2.2 μm, and the particle diameter of the silver metal particles shown in Figure 3 is 1.5 μm, but a case was shown in which one fine particle was not completely polymerized on the surface of the silver particle.

[0032] Example 3 3 g of Tween and 15 μg of 10-20 nm nano silver were mixed in water to obtain a first dispersant, and PVP was dissolved in 35 mL of water to prepare a solution with a mass concentration of 6.5% to obtain a second dispersant. The first and second dispersants prepared above were mixed and stirred uniformly to obtain a dispersant system, and the solution was kept at a constant temperature of 25 ° C.

[0033] In addition, 15 g of VC was added to a beaker containing a certain amount of water and stirred uniformly, and then the resulting VC solution was added to the dispersant system, and then a solution containing 10 g of silver nitrate with a mass concentration of 20% was quickly added while stirring, and after the reaction, oleylamine was added to obtain silver metal particles with a pore structure. The microscopic results are shown in Figure 4.

[0034] Example 4 5g of sodium alkylbenzenesulfonate was dissolved in water and mixed with 10μg of 10-90nm nano silicon dioxide to obtain a first dispersant, and 3.5g of polyvinylpyrrolidone was dissolved in 35mL of water to prepare a solution to be used as a second dispersant. The first and second dispersants produced above were mixed and stirred uniformly to obtain a dispersant system, and the solution was kept at a constant temperature of 30℃.

[0035] Next, while stirring the dispersant system, a 28% solution containing 17 g of a 30% silver nitrate solution and 5 g of aqueous hydrazine was added thereto, and after the reaction, sodium stearate was added to obtain silver metal particles having a pore structure.

[0036] Comparative Example 1 15 μg of 10 to 20 nm nanosilver was mixed with PVP to prepare a solution with a mass concentration of 9% to serve as a dispersant, and the solution was kept at a constant temperature of 25°C.

[0037] 25 g of VC was added to a beaker containing a certain amount of water and stirred uniformly, and then the resulting VC solution was added to the dispersant system. Next, a solution containing 15 g of silver nitrate with a mass concentration of 25% was quickly added while stirring. After the reaction, linoleic acid was added to obtain silver metal particles.

[0038] The metal particles in the above-mentioned Examples 1 to 4 and Comparative Example 1 were cut. As described above, FIB-SEM technology was adopted as a method for cutting metal particles, and the metal particles were cut using a gallium particle focused ion beam, and each metal particle was cut so that the cross section of the metal particle was exposed, and then the cross section of the particle was observed using a scanning electron microscope (SEM). A cross-sectional schematic diagram of the metal particles obtained in Example 1 is shown in FIG. 5, cross-sectional schematic diagrams of the metal particles obtained in Example 2 are shown in FIG. 6 and FIG. 7, cross-sectional schematic diagrams of the metal particles obtained in Examples 3 and 4 are shown in FIG. 8 and FIG. 9, and a cross-sectional schematic diagram of the metal particles obtained in Comparative Example 1 is shown in FIG. 10.

[0039] In the SEM observation, orthogonal projection was used to identify various contrasts in the images, and the particle size, cross-sectional area and void area of ​​the silver metal particles in Figures 5 to 10 were calculated under various contrasts, and the results are shown in Table 1 below. Among these, the measurement results were calculated from the average value of three measurements, and the void ratio is calculated as void area / cross-sectional area of ​​silver metal particle.

[0040] [Table 1]

[0041] As can be seen from the results of Figures 5 to 10 and Table 1, the porosity of the silver metal particles obtained by the method of Comparative Example 1 is low, reaching only 0.25%, whereas the silver metal particles produced by the exemplary methods of the present invention (Examples 1 to 4) have a large specific surface area, a high shrinkage ratio, a high sphericity, and a porosity of at least 2.97 or more, and can even reach 11.16%.

[0042] Also, Figure 11 is a partially enlarged view of Figure 9, which clearly shows the voids in the metal particles of the present invention, which have two types: voids inside the newly generated one-stage metal microparticles and large voids between the metal microparticles formed in the metal microparticle polymerization process during the two-stage reaction.

[0043] Although the preferred embodiments of the present invention have been described in detail above, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, a number of simple modifications can be made to the technical solutions of the present invention, and all of these simple modifications fall within the protection scope of the present invention.

[0044] It should be noted that the specific technical features described in the above specific embodiments can be combined in any suitable manner as long as there is no contradiction, and in order to avoid unnecessary duplication, the present invention does not separately describe various possible combination methods.

[0045] Furthermore, any combination between various different embodiments of the present invention is possible, and as long as it is not contrary to the spirit of the present invention, it should be considered as the contents disclosed in the present invention.

Claims

1. a step of reacting a metal source-containing oxidizing agent with a reducing agent in the presence of a first dispersing agent and a second dispersing agent to obtain the metal particles; the first dispersant comprises a first low molecular weight organic solvent and at least one type of nanoparticles; and The method for producing metal particles, wherein the second dispersant contains a second organic solvent having a high molecular weight.

2. 2. The method according to claim 1, wherein the first organic solvent is an organic solvent having a molecular weight of 1200 Da or less, the second organic solvent is an organic solvent having a molecular weight of more than 1200 Da, and the first organic solvent and the second organic solvent are each independently at least one selected from organic acids, gum arabic, ester-based, ether-based, ether ester-based, ketone-based, amine-based, alcohol-based, pyridine-based, and pyrrolidone-based organic solvents.

3. The method according to claim 2, wherein the first organic solvent is at least one selected from fatty acids and salts thereof, alkyl sulfuric acids and salts thereof, alkylbenzene sulfonic acids and salts thereof, linear alkylbenzene sulfonic acids and salts thereof, maleic acid and salts thereof, 1-vinylpyrrolidone, N-vinylpyrrolidone, methylpyrrolidone, polyoxyethylene lauryl ether triethanolamine sulfate, octylamine, ethanol, polyethylene glycol, alkyl triethanol sulfate, glycerol, alkyl ether sulfate ester salts, sorbitol, sorbitan, polysorbate (Tween), sorbitan fatty acid ester (Span), lecithin, polysorbate dialkyldimethylammonium chloride, alkylpyridinium chloride, polyoxyethylene alkyl ether (AE), polyoxyethylene alkyl phenyl ether (APE), alkyl carboxybetaine, and sulfobetaine.

4. 3. The method according to claim 2, wherein the second organic solvent is at least one selected from gum arabic, a formaldehyde condensate of a naphthalene sulfonate, a polyacrylate, a copolymer salt of a vinyl compound and a carboxylic acid monomer, carboxymethyl cellulose, polyvinyl alcohol, polyethylene glycol, a polyacrylic acid partial alkyl ester and / or a polyalkylene polyamine, polyethyleneimine and / or an aminoalkyl methacrylate copolymer, polyvinylpyrrolidone, polystyrene sulfonic acid, polyacrylic acid, a polyoxyethylene alkyl ether, and a polyoxyethylene alkyl phenyl ether.

5. The method according to claim 1, wherein the nanoparticles are at least one selected from organic nanoclusters, non-metal oxides, metal elements, metal oxides, or inorganic metal salts, and preferably the size of the nanoparticles is 0.1 to 90 nm.

6. 6. The method of claim 5, wherein the organic nanoclusters are at least one selected from cellulose and organic carbohydrates, the non-metal oxide is at least one selected from oxides of silicon, carbon, and nitrogen, the metal is at least one selected from gold, silver, platinum, palladium, cobalt, copper, nickel, and zinc, the metal oxide is at least one selected from oxides of gold, silver, platinum, palladium, cobalt, copper, nickel, and zinc, and the metal inorganic salt is selected from metal sulfates or nitrates.

7. The method of claim 1 , wherein the metal source-containing oxidizing agent is at least one selected from inorganic metal salts, organic metal salts, and metal complexes.

8. The method of claim 7, wherein the metal is at least one of gold, silver, platinum, palladium, cobalt, copper, nickel, and zinc.

9. 2. The method according to claim 1, wherein the reducing agent is at least one selected from the group consisting of hydrazine-based, amine-based, organic acid and its salt-based, alcohol-based, aldehyde-based, hydrogen compound-based, transition metal salt-based, pyrrolidone-based, and hydroxylamine-based reducing agents.

10. 2. The method of claim 1, wherein the weight of the first dispersant is 0.1-40 wt %, the weight of the second dispersant is 1-60 wt %, and the weight of the nanoparticles is 0.0001-1.0 wt %, relative to the weight of the metal in the oxidizer.

11. The method of claim 1 further comprising the step of adding a flocculant after or before the redox reaction.

12. The method of claim 11 , wherein the flocculating agent is selected from a lipid compound, a carboxylic acid-based compound, or an inorganic salt.

13. The method according to claim 12, wherein the lipid compound is a saturated fatty acid and a salt thereof, or an unsaturated fatty acid and a salt thereof, and preferably the saturated fatty acid is at least one selected from caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, and arachidic acid, the unsaturated fatty acid is at least one selected from oleic acid, linoleic acid, sorbic acid, linolenic acid, and arachidonic acid, the carboxylic acid compound is at least one selected from compounds having a carbon-carbon double bond, dicarboxy compounds, and dihydroxy compounds, and the inorganic salt is at least one selected from sulfates, nitrates, and ammonium salts.

14. Metal particles produced by the method according to any one of claims 1 to 13.

15. The metal particles according to claim 14, wherein the porosity of the metal particles is 2.97% or more.

Citation Information

Patent Citations

  • Method for preparing metal powder by utilizing nano crystal seed induction

    CN105436517A

  • Metal particle and preparation method and application thereof

    CN114082938A

  • Silver powder, producing method therefor, and conductive paste

    JP2020056050A